Demographic Characteristics and Etiology of Hydrocephalus Patients attended at Tertiary Care Hospital in Bangladesh (Journal of National Institute of Neurosciences Bangladesh, 2017)
Background: Hydrocephalous can occur at any age. Objectives: The purpose of the present study was to see the Demographic Characteristics and Etiology of Hydrocephalus Patients. Methodology: This cross sectional study was conducted in the Department of Neurosurgery at Bangabandhu Sheikh Mujib Medical University, Dhaka from April 2009 to September 2010 for a period of one and half year. Patients presented with obstructive hydrocephalus at any age with both sexes were included as study population. Detailed socio-demographic history as well as the associated etiological factors was recorded in pre designed data collection sheet. Result: A total number of 60 obstructive hydrocephalous patients were recruited for this study after fulfilling the inclusion and exclusion criteria. The mean age with SD was 17.95±19.15. Acquedctal stenosis was the most common etiology of hydrocephalous which was 31(51.7%) cases followed by posterior fossa midline tumour, CPA tumour and pineal region tumour which were 14 (23.3%) cases, 9(15.0%) cases and 6(10.0%) cases respectively. Conclusion: Obstructive hydrocephalous is most commonly found in younger age group which is caused by acquedctal stenosis. Journal of National Institute of Neurosciences Bangladesh, 2015;1(2): 47-49